(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to investigate the relationship between FDG uptake and clinicopathological characteristics of invasive breast carcinoma-no special type in the present study.Materials and Methods: One hundred seventy invasive breast carcinoma-no special type cases who underwent PET-CT before surgery between 2011-2019 were included in the study. The clinicopathological features and SUVmax of the patients were compared.Results: We observed a strong relationship between the size, grade, pathological stage groups and SUVmax of the tumors and revealed that the SUVmax increased as the size, grade, and pathological stage groups of the tumors increased (p0.001). Carcinomas with high Ki67 proliferation index and ER and PR negative carcinomas exhibited higher SUVmax (p0.001). Triple negative and HER2-enriched molecular subtypes had distinctly higher SUVmax than Luminal A and Luminal B ones (p0.001). HER2-enriched tumors, the cases that were 40 years old and advanced stage designated higher SUVmax (p0.05). Conclusion: It is observed that invasive breast carcinoma-no special type with good prognostic factors have low SUVmax, while carcinomas with poor prognostic features have high SUVmax. It can be suggested that PET/CT can be use to predict the prognosis of invasive breast carcinoma-no special type.